Urban-rural consumption differences among the elderly in developed regions: Evidence from Zhejiang, China - Yanhong Yin; Li’ao Huang; Qiuyan Han (PLoS ONE, 2025)
This study examines the consumption patterns of older adults and the urban-rural disparities in Zhejiang Province, a highly developed yet rapidly aging region of China. A total of 276 valid samples were obtained from Ningbo, Hangzhou, and Wenzhou through a mixed approach combining online snowball sampling with offline random sampling. A LASSO regression model was employed to assess the effect of residence while controlling for socioeconomic variables. The results indicate that urban older adults spend significantly more than their rural counterparts, with average monthly consumption reaching 3,980 RMB compared to 2,502 RMB. Urban residence was associated with an increase of 995 RMB in total expenditure, with higher spending observed on housing, food, daily necessities, leisure and education, and health rehabilitation. Although rural respondents expressed strong interest in leisure, education, and health services, their actual expenditures in these categories were much lower, revealing a gap between intentions and behavior. Offline consumption remains dominant, but online consumption is expanding slowly. Digital exclusion persists, particularly in rural areas, due to limited literacy, complex interfaces, and unstable internet access. These findings suggest that elderly consumption is influenced not only by income but also by structural inequalities, health constraints, and digital inclusion. Policy measures should therefore strengthen rural healthcare, expand cultural and recreational opportunities, and promote elder-friendly digital platforms. Programs such as healthcare vouchers and targeted subsidies could help narrow the gap between intention and capability. This study provides preliminary exploratory insights into inclusive policies that may foster the sustainable development of China’s silver economy.